Impact of Specific Yoga Module with special reference to Bhramari, Trataka and Jala neti on attention among Archers - Yadav, Nidheesh; Rathore , Vipin (International Research Journal of Ayurveda & Yoga, 2022)
Introduction: Attention is a complex cognitive phenomenon of selecting significant issues and disregarding those which are less significant characterizes achievement in sports, including archery. This study aimed to find out the effect of specific yoga modules with special reference to Bhramari Pranayama, Trataka, and Jala Neti, on attention among Archers. Material and methods: An experimental-control group design with a random sampling method having inclusion criteria for the participant obtained 50 individuals ranging from 18 to 25 years of age from Bhopal; were included in the study. Result: The 25 participants from the experimental group showed a high level of significance (p<0.05) after practicing specific yoga module with Bhramari, trataka, and jala neti for an hour and archery for 2 hours every day, except Sundays for 12 weeks in contrast to the control group were only yoga modules designed for the experimental group were not exposed. Discussion: The study suggests that a specific yoga module with special reference to Bhramari, trataka and, jala neti has a positive effect on increasing the shooting score and reducing errors in the Eye-Hand Coordination Test. Yoga can be practiced in a daily routine to increase the level of attention substantially.